Some aspects of the pathogenesis and treatment of back pain - A. N. Barinov (Неврология, нейропсихиатрия, психосоматика)
The author analyzes the data available in the literature on and his clinical experience in diagnosing and treating back pain. It is shown that none of the surgical, pharmacological, physical, or psychological treatments singly used for chronic pain can effectively equal a multidisciplinary approach employed in specialized pain clinics when all the above approaches mutually intensify each other. At the same time the risk of adverse reactions is substantially lowered by the smaller doses of drugs and the shorter course of their use.